Determinants of Quality of Nursing Work Life among Staff Nurses at a Public Hospital in Indonesia: A Cross-Sectional Study - Lilis Suryani (STIKep PPNI Jawa Barat, 2026)
Background: The quality of nurses’ work life has received increasing attention because it is associated with workforce sustainability, nurse well-being, and healthcare outcomes. In Indonesian public hospitals, nurses may face resource constraints, high service demands, and organizational pressures that can affect their work experiences. Evidence on the simultaneous contribution of individual, organizational, and psychological factors to Quality of Nursing Work Life (QNWL) in public-hospital nurses remains limited. Objective: This study aimed to identify factors associated with Quality of Nursing Work Life among staff nurses at Karawang General Hospital, Indonesia. Methods: An analytical cross-sectional study was conducted from November 2025 to April 2026 among 100 staff nurses working in inpatient wards, intensive care units, emergency departments, and outpatient services. Participants were selected using proportional stratified random sampling across service units. Data were collected using self-administered questionnaires, including the Brooks Quality of Nursing Work Life Survey and adapted instruments assessing workload, managerial support, reward system, work environment, job satisfaction, and organizational commitment. Data were analyzed using descriptive statistics, bivariate tests appropriate to variable type, and multiple linear regression with SPSS version 25. Results: More than half of the participants reported moderate QNWL (57%), followed by high QNWL (28%) and low QNWL (15%). QNWL was significantly associated with age (p = 0.041), educational attainment (p = 0.032), and length of employment (p = 0.018). Organizational factors were also significantly associated with QNWL, including workload (p = 0.001), managerial support (p < 0.001), reward system (p = 0.005), and work environment (p = 0.003). Psychological factors, namely job satisfaction (p < 0.001) and organizational commitment (p = 0.001), were significantly associated with QNWL. In the adjusted regression model, managerial support had the largest standardized coefficient (β = 0.524, p < 0.001), followed by job satisfaction (β = 0.411, p = 0.001), workload (β = −0.321, p = 0.002), and work environment (β = 0.298, p = 0.004). Conclusion: Organizational and psychological factors were important correlates of QNWL among staff nurses. Managerial support showed the strongest association in the adjusted model, suggesting that leadership development, structured feedback, workload review, and supportive work-environment initiatives may help create conditions for improved nurses’ work life. Because of the cross-sectional design, the findings should be interpreted as associations and not as causal effects